2011
DOI: 10.1038/nchembio.534
|View full text |Cite
|
Sign up to set email alerts
|

A whole-organism screen identifies new regulators of fat storage

Abstract: The regulation of energy homeostasis integrates diverse biological processes ranging from behavior to metabolism and is linked fundamentally to numerous disease states. To identify new molecules that can bypass homeostatic compensatory mechanisms of energy balance in intact animals, we screened for small molecule modulators of C. elegans fat content. We report on several molecules that modulate fat storage without obvious deleterious effects on feeding, growth, and reproduction. A subset of these compounds als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 51 publications
2
78
0
Order By: Relevance
“…In preliminary experiments, we examined the effect of berberine, a known lipid modulator, by Nile Red staining 9,17) and confirmed that it has a lipid-reducing effect. We further validated the effect of berberine by Oil Red O stain, since it is a more accurate proxy for major fat stores in the subcellular compartments of the worm.…”
Section: Resultsmentioning
confidence: 90%
“…In preliminary experiments, we examined the effect of berberine, a known lipid modulator, by Nile Red staining 9,17) and confirmed that it has a lipid-reducing effect. We further validated the effect of berberine by Oil Red O stain, since it is a more accurate proxy for major fat stores in the subcellular compartments of the worm.…”
Section: Resultsmentioning
confidence: 90%
“…ImageJ (Schneider et al 2012) was used to quantify the fluorescence intensity of whole body, and the background signals were subtracted. For measuring the intestinal expression of fat-6p::fat-6::GFP or fat-7p::GFP, the first anterior intestinal cells were quantified as described previously (Lemieux et al 2011). …”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…For example, the Nile Red dye, which selectively stains lipid droplets, has been used in live C. elegans to identify genes (Ashrafi et al, 2003) or small molecules (Lemieux et al, 2011) that regulate fat storage. In another attempt to understand the basic biology of lipid droplets formation, a screen was carried out in human liver cells that were stained with a lipid droplet imaging kit to identify microRNAs (miRNAs) that regulate their accumulation (Whittaker et al, 2010).…”
Section: Lipid Labelingmentioning
confidence: 99%